the private sector in Algeria and the question of socio-economic development. Towards a sociological analysis of the development landscape. - Mohamed Lamine HAICHOUR (Social Sciences Journal, 2021)
The private sector has emerged as the most important economic asset in recent times. Many countries were quick to introduce economic reforms, abandoning the unproven base economy The pace of these reforms has increased day by day, especially as decision makers are convinced of the importance of the private sector , Consider it a lifeline for the economic problems of most public institutions, This will allow for the emergence of a new scenario of a limited economic role for the State and its gradual withdrawal from activity, It's just a tool of guidance and surveillance that allows the private sector to be activated in accordance with the principles of economic freedom.As part of the modernization of the economic machine, the production and performance processes were activated, Free institutions from indiscriminate management and qualitative change in productive relationships, The Algerian State has resorted to the capitalist approach as an alternative to re-engineering the economic home This study aims to illustrate the role of the private sector in the recovery of the socioeconomic body.,